Phenotyping analysis of rice lodging based on a nondestructive mechanical platform - LÜ Mengqi; Sunghwan JUNG; MA Zhihong; WAN Liang; SUN Dawei; CEN Haiyan (浙江大学学报. 农业与生命科学版, 2023)
Traditional rice lodging measurements are time-consuming and destructive to rice plants. This study thus developed an easy-to-implement and nondestructive mechanical platform for phenotyping analysis of rice lodging, which can monitor the lodging-resistant characteristics of rice in different growth periods. The lodging measurements were conducted at the jointing stage, booting stage and heading stage from August 15th to September 21st, 2019. The force and displacement were measured from two different directions using the lodging measuring platform with a force sensor, which were used to calculate the dynamic bending stiffness coefficient (KEI) of rice. Meanwhile, RGB images were collected from the mechanical platform, which were applied to calculate the projected area and the center of force (CoF). The results showed that the KEI values of lodging-resistant cultivars (Beidao 1 and Shennong 9816) were different from those of lodging cultivars (Yueguang and Qiuguang), which can reflect rice’s lodging resistance in the growth period. In addition, we found that the average distances between CoF and the root of lodging cultivars within the RGB images were larger than those of lodging-resistant cultivars and easily led to rice instability. This study can provide valuable information for rice lodging monitoring and precision breeding.